Suffering of The Righteous People in The Perspective of Religious Phenomenology - Agustinus Wisnu Dewantara (Al-Albab, 2020)
Suffering is the reality of religious people, so suffering is an important theme of almost all religions. The negativity and depression involved with suffering invite religions to discuss it. Suffering is the constitutive reality of all humans. All human beings must suffer, but their faith makes them have a different perspective in reacting to it. This paper wishes to examine the theme of suffering in hermeneutic and phenomenology studies. The research model used in this paper is a qualitative model with as much as possible using hermeneutics by comparing several texts and understanding about suffering. The expected goal of deepening this theme is to find a more comprehensive understanding of suffering as a believer, and finally be able to unite spiritual suffering in the light of God. Life is not to suffer and die silly. Life is also not filled with the solitude of suffering merely, because clearly God created man not to make him suffer. Suffering is not sent to destroy the righteous, but it is suffering that will purify the righteous even more. Suffering is the reality of religious people, so suffering is an important theme of almost all religions